Early Childhood Perceptions of Diversity: A Case of Addressing Multicultural Education in the Classroom - Ashley McRae; Jason Brent Ellis (University of Windsor, 2012)
This evaluation-based case study research focused on the on how elementary school children perceived diversity in a homogeneous community and analyze how teaching practices can act as an agent to toward and against multicultural pluralism in the classroom. Visual-based methods were used with participants as first grade children were asked to take pictures in the school setting of what they interpreted as diverse. Findings suggested that early childhood students saw the physical manifestation of diversity in many ways and hidden curriculum in the way teachers choose to display diversity in the classroom may hold the key to unlocking a more multicultural curriculum.